Language learning motivation in collaborative online international learning: an activity theory analysis - Tomoe Nishio; Chie Fujikake; Masataka Osawa (University of Groningen Press, 2020)
This study investigated the development of language learning motivation in an American student of Japanese, Jason, during a mobility-based Collaborative Online International Learning (COIL) project with a Japanese institution. Drawing on an activity theory perspective, this qualitative case study analyzed the student artifacts of the project as well as of interview and fieldnote data to illustrate the transformational process. Findings demonstrate how Jason's pre-COIL motives (pragmatic, cultural, linguistic, and intellectual) were negotiated while participating in the COIL project. Through interacting with Japanese students, Jason's preexisting linguistic demotivation was reversed by his positive reevaluation of his own oral skills, which enhanced his desire for higher proficiency. The project also stimulated Jason's intellectual motive to learn Japanese using technology, leading to his autonomous choice to research language learning and technology, and to create a podcast. It is argued that Jason's motivation for Japanese learning was enhanced through the social process, during which motives were transformed along with personal significance to him.